Assessment of genetic diversity in extraearly Strigaresistant tropical inbred lines using multivariate analysis of agronomic data - Badu-Apraku, Baffour; Menkir, A.; Lum, A.F. (2005)
An assessment of the genetic diversity among extra-early maturing maize inbred lines would be useful for identifying closely related lines, in determining the variation in genetic similarity among genotypes that show no variation for parentage and in planning crosses between genetically divergent parents. Genetic diversity in 65 extra-early maturing maize inbred lines was studied under Striga-infested and Striga-free conditions using the principal component analysis (PCA) and Ward's minimum variance cluster analysis. Based on the similarity of the quantitative characters, cluster analysis of the inbreds produced four major clusters under both Striga-infested and Striga-free conditions. However, the inbred lines assigned to each cluster under Striga infestation differed from those under Striga-free conditions. Based on the preliminary grouping of the inbreds, it may be predicted that the selection of specific combinations of inbred lines for the development of hybrids, or synthetics, or for introgression into breeding populations may best be done by selecting parents that combine high grain yield with reduced Striga damage symptoms and numbers of emerged Striga plants, as well as high numbers of ears per plant in each cluster. The most important variables for the classification of the inbreds under Striga infestation were grain yield, EPP, Striga emergence counts at 8 and 10 WAP and Striga damage syndrome rating at 10 WAP.